2016
DOI: 10.1080/13632752.2016.1165978
|View full text |Cite
|
Sign up to set email alerts
|

The antithesis of inclusion? The emergence and functioning of ADHD special education classes in the Swedish school system

Abstract: The neuropsychiatric paradigm has substantial impact on schools. The increase in the number of pupils being diagnosed with attention-deficit/hyperactivity disorder (ADHD) is an expression of the medicalization of deviance. There is also an increase in educational classes specially designed to meet the needs of children with ADHD. This is contrary to the notion of inclusion and in conflict with the Swedish school law. Thus, it is important to obtain knowledge about Swedish ADHD classes.A questionnaire was sent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 21 publications
2
22
0
3
Order By: Relevance
“…In Sweden, a recent national-survey study revealed the existence of classes specifically designed for students with ADHD (Malmqvist and Nilholm 2016), which is contrary to the notion of inclusion and to national policy (Hjorne and Evaldsson 2015). Little is known about why these ADHD classes have been established in some municipalities and not in others.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In Sweden, a recent national-survey study revealed the existence of classes specifically designed for students with ADHD (Malmqvist and Nilholm 2016), which is contrary to the notion of inclusion and to national policy (Hjorne and Evaldsson 2015). Little is known about why these ADHD classes have been established in some municipalities and not in others.…”
Section: Introductionmentioning
confidence: 92%
“…Swedish municipalities (There are 290 municipalities ranging from 2,400 to 864,000 inhabitants in 2011, Statistics Sweden 2012) have a certain degree of freedom in interpreting state-governed policy, but they must follow educational legislation. The aforementioned nationwide-survey study sent to all municipalities (234/308, response rate 76%) is an important backdrop to the present study (Malmqvist and Nilholm 2016). The survey revealed that as many as 40 municipalities (17%) had classes specifically designed for students with ADHD.…”
Section: Adhd Special Education Classes In the Swedish School Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though mainstream schools are open for children with disabilities, special classes are still being formed, e.g. ADHD special education classes in the Swedish school system (Malmqvist, Nilholm, 2016) or special classes for pupils with ASD in Ireland (McCoy et al, 2014).…”
Section: Beata Papuda-dolińskamentioning
confidence: 99%
“…ADHD behaviour tends to be seen as the inverse of successful behaviour in schools (Hinshaw and Scheffler 2014). According to Malmqvist and Nilholm (2016), children showing 'disorderly' attributes that are associated with ADHD challenge schools and teachers because their behaviour may, for instance, disrupt classroom peace and order. Schools and teachers generally play an important role in initiating the first steps towards a childhood disorder classification (Sax and Kautz 2003;Langley et al 2010;Russell, Moore, and Ford 2016;Moore et al 2017).…”
Section: Introductionmentioning
confidence: 99%